TREN DAN DISTRIBUSI TIMBULAN SAMPAH SERTA SUMBERNYA PADA KABUPATEN DAN KOTA DI INDONESIA - Purba, Seri Ulina; Faradiba, Selly; Sitanggang, Jhon Wesly (IKES Payung Negeri Pekanbaru, 2025)
Waste management remains a strategic issue in Indonesia along with the increasing population, urbanization, and changes in consumption patterns that contribute to the rise in annual waste generation. This study aims to analyze waste generation trends and the distribution of its sources in districts and cities in Indonesia during the period 2020–2024. The research design uses a quantitative descriptive approach with secondary data from the National Waste Management Information System (SIPSN). The analysis is conducted through tabulation and graphical visualization to illustrate the comparison of trends and the contribution of waste sources. The research results show that the waste generation in urban areas is higher than in rural areas, with a total of 9.03 million tons in the city and 7.38 million tons in the district in 2020, increasing to 9.25 million tons in the city and 7.57 million tons in the district by 2024. The source of waste is dominated by households, with contributions increasing from 58.0% to 73.9% in the district, and from 37.8% to 51.1% in the city. Contributions from other sources such as markets, offices, public facilities, and areas are relatively small, while the percentage of areas that do not report data is still quite high, especially in the city. These results indicate that households are the main source of waste, so community-based management, increased public awareness, and improvements in the data reporting system are key to achieving sustainable waste management. Keywords: District, city, waste, source, trend